2023
DOI: 10.3390/antiox12050985
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury Alters Cerebral Concentrations and Redox States of Coenzymes Q9 and Q10 in the Rat

Abstract: To date, there is no information on the effect of TBI on the changes in brain CoQ levels and possible variations in its redox state. In this study, we induced graded TBIs (mild TBI, mTBI and severe TBI, sTBI) in male rats, using the weight-drop closed-head impact acceleration model of trauma. At 7 days post-injury, CoQ9, CoQ10 and α-tocopherol were measured by HPLC in brain extracts of the injured rats, as well as in those of a group of control sham-operated rats. In the controls, about the 69% of total CoQ wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…When these processes persist, the endogenous antioxidant system becomes depleted as brain endogenous antioxidants like superoxide dismutase (SOD) or glutathione (GSH) work to remove and neutralize ROS/RNS. Only a few studies have explored antioxidant depletion following TBI [ 26 , 27 , 43 , 44 ]. However, to our knowledge, no studies to date have reported extensive and chronic antioxidant depletion in human subjects in response to mTBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When these processes persist, the endogenous antioxidant system becomes depleted as brain endogenous antioxidants like superoxide dismutase (SOD) or glutathione (GSH) work to remove and neutralize ROS/RNS. Only a few studies have explored antioxidant depletion following TBI [ 26 , 27 , 43 , 44 ]. However, to our knowledge, no studies to date have reported extensive and chronic antioxidant depletion in human subjects in response to mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…A few novel studies (2020-present) have begun to explore antioxidant levels following TBI. In a rat model of TBI, coenzyme-q9, coenzyme-q10, and α-tocopherol were found to be significantly reduced in brain tissue one-week post-severe TBI, although no differences were observed following mTBI [ 26 ]. Another study measured total antioxidant capacity in serum in humans one-week post-severe TBI and reported it may be indicative of survival outcomes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…FF supernatants (500 µL) were light-protected, deproteinized by the addition of 1 mL of HPLC-grade acetonitrile, vortexed for 60 s and placed in a water bath for 1 h at 37 • C. As previously shown, this procedure allows the quantitative recovery of fat-soluble compounds in biological samples [49][50][51][52]. Protein-free FF were obtained by centrifugation at 20,690× g for 15 min at 4 • C and then saved at −80 • C until the HPLC analysis of fat-soluble compounds, including free and bound bilirubin.…”
Section: Samples Processing and Hplc Assay Of Bilirubin In The Fat-so...mentioning
confidence: 99%